Is corifollitropin alfa effective in controlled ovarian stimulation among all poor ovarian responders? A retrospective comparative study. (3rd October 2019) - Andrisani, A.; Marin, L.; Ragazzi, E.; Donà, G.; Bordin, L.; Dessole, F.; Armanini, D.; Esposito, F.; Vitagliano, A.; Sabbadin, C.; Ambrosini, G.
Abstract: Several studies have compared the effectiveness of corifollitropin alfa versus daily gonadotropins in poor ovarian responders (PORs) undergoing controlled ovarian stimulation (COS), showing conflicting results in terms of IVF outcomes. Given the heterogeneity of patients included in the classification of POR according to 'Bologna criteria', the aim of this study was to evaluate the impact of corifollitropin alfa in two different categories of POR distinguished according to patients' antral follicle count (AFC). We retrospectively evaluated 104 infertile POR, split into two groups according to AFC (Group A ≤ 5; Group B > 5) and subgroups according to the ovarian stimulation regimen (corifollitropin alfa plus daily gonadotropins (Subgroup 1) versus daily gonadotropins alone (Subgroup 2)). Outcome measures were total oocytes, MII oocytes, total embryos, follicular output rate (FORT), implantation rate (IR), clinical pregnancy rate (CPR), miscarriage rate (MR), and live birth rate (LBR). Subgroup A1 experienced a lower number of total oocytes, MII oocytes, total embryos, and FORT ( p < .05) in comparison to Subgroup A2, while no difference was found when comparing Subgroups B1 and B2. No difference was found between subgroups even in terms of IR, CPR, MR, and LBR. In conclusion, corifollitropin alfa may be as effective as daily gonadotropins in POR with AFC > 5 undergoing COS, while it might be inferior to daily gonadotropins in POR with AFC ≤ 5.